Muscle Bmal1 is Dispensable for the Progress of Neurogenic Muscle Atrophy in Mice. (19th August 2016) - Nakao, Reiko; Shimba, Shigeki; Oishi, Katsutaka
Global deletion of aryl hydrocarbon receptor nuclear translocator-like ( Arntl ; also known as Bmal1 ), a molecular component of the circadian clock, resulted in an extreme loss of muscle mass. However, the functional role of muscle BMAL1 has not been elucidated. Here, we used muscle-specific Bmal1 knockout mice to determine whether disrupting the muscle clock exacerbates muscle atrophy induced by sciatic denervation or aging. The muscle mass of wild-type and muscle-specific Bmal1 knockout mice decreased to a similar extent at seven days after denervation, although Bmal1 ablation partly attenuated the upregulation of genes encoding muscle atrophy-related ubiquitin ligases, muscle atrophy F-box (MAFbx) and muscle RING finger 1 (MuRF1). A comparison of adult and elderly mice aged 7 – 8 and 23 – 24 months, respectively, confirmed that ablating muscle Bmal1 scarcely affected the extent to which aging induced the loss of muscle mass. Muscle Bmal1 minimally affected the progression of muscle atrophy caused by sciatic denervation or aging.